2004
DOI: 10.1038/sj.mp.4001532
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in schizophrenia: evidence for compromised brain metabolism and oxidative stress

Abstract: Transcript changes and altered pathways in schizophrenia prefrontal cortex. (a) Mitochondria are the most affected cellular components at the transcript level in schizophrenia. Cellular localization of the significantly altered genes (both up-and downregulated) that passed RMA and filtering procedures were analyzed and visualized using GO Surfer (http://biosun1.harvard.edu/complab/gosurfer/). Branches and nodes represent pathways containing greater than five genes. Significantly altered 'cellular components' (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
251
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(289 citation statements)
references
References 0 publications
29
251
0
8
Order By: Relevance
“…Our study and another two studies (Table 3) also found another protein related to oxidative stress, peroxiredoxin-1 (PRDX1), to be downregulated, reinforcing the concept of a reduced response to oxidative stress [58,59].…”
Section: Resultssupporting
confidence: 79%
“…Our study and another two studies (Table 3) also found another protein related to oxidative stress, peroxiredoxin-1 (PRDX1), to be downregulated, reinforcing the concept of a reduced response to oxidative stress [58,59].…”
Section: Resultssupporting
confidence: 79%
“…Mitochondria being the major source and target of ROS, play a pivotal role during ageing and neurodegenerative diseases (Prabakaran et al 2004;Balaban et al 2005;Lin and Flint Beal 2006). It is evident that CR is effective at mitochondria to lower the ROS levels (Bevilacqua et al 2004) by modulating respiratory chain activities and enhanced biogenesis of mitochondria with low membrane potential (Barja 2004;Lopez-Lluch et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In anxiety this is supported by -omics findings in mouse models [21,22,33]. Proteomics and metabolomics studies in schizophrenia [19,34,35,36,37] and depression [38] have also reported alterations for protein and metabolite oxidative stress markers.…”
Section: Proteomics and Metabolomics Studies In Psychiatric Disordersmentioning
confidence: 50%